Genetic Diversity of Jatropha spp. Germplasm Based on Morphological and Molecular Markers - Rerenstradika T. Terryana; Kristianto Nugroho; Karden Mulya; I Made Tasma; Puji Lestari (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2019)
Germplasm of Jatropha spp. with high genetic diversity is needed to develop a new superior variety of Jatropha spp. Morphological and molecular characterizations are important to support development of their superior hybrid varieties. The aims of this study were to identify Jatropha spp. accesion potential for genetic improvement using morphological characters and analyze their genetic diversity using SSR markers. A total of eight genotypes of Jatropha spp. originated from several localities in Indonesia and Thailand was observed. Results showed that accessions of Jatropha spp. were varied in morphological and molecular characters. Based on principle component analysis, characters of stem color, leaf veins, leaf shapes, flower position, total branch number, productive branch number, petiole color, and petal color contributed most to the total diversity. Based on oil seed content, potential accessions identified for further genetic improvement were J. podagrica (34.63%) and J. curcas (29.64%). The results of molecular analysis showed that high allele variation (3–7 alleles) was observed among Jatropha spp. accessions with an average allele number of 4.12 and the average Polymorphism Information Content (PIC) value was 0.57 (0.46–0.77). Three SSR markers showed PIC value >0.5 indicating that these markers were informative for genetic diversity detection of Jatropha spp. The phylogenetic analysis showed that seven accessions of Jatropha spp. could be divided in two groups at similarity coefficent of 0.53. Results of genetic diversity analysis in this study should be useful for proper identification and selection for appropriate parents to assist in breeding of Jatropha spp. in Indonesia.